Teachers' perceptions of bullying with a consideration of the bystanders' role : a study in the Finnish context - Triantafyllou, Aikaterini (My University, 2020)
This study analyses teachers’ perceptions of bullying with a consideration of the bystanders’ role. Ten Finnish teachers from all school levels were inquired about their perceptions on school bullying. Additionally, the teachers were asked to evaluate what is the bystanders’ contribution. Thematic analysis revealed ten themes: 1) Not bully-free schools 2) Teachers: general strategies 3) Teachers’ feelings 4) Specific teacher practices 5) Innovative practices 6) Shifting bystander roles 7) Teachers’ perceptions of outsiders 8) Parental involvement 9) Gender and age 10) Skilful and loner- bully and victim. Some main findings of this study are: Finnish schools are described as facing many bullying problems. Teachers disclose they resort to their colleagues for help. Students are described as changing roles during or even after the incident or in another incident. In one occasion they stay uninvolved, for example, and in another they ally themselves with the bully. According to the teachers, parents are mainly responsible for educating their children about bullying. Parents should instruct their children not to bully and how to defend themselves and others when bullying occurs. Finally, according to one fundamental course of action used as an anti-bullying intervention, uninvolved students (outsiders) should be turned to defenders. The findings of this study though show that this aim has not been met with success so far. Some ideas for future intervention and prevention plans are being presented.
Keywords: teachers, preceptions of school bullying, bystanders, outsiders